(untitled) (Psychology Travelogs, 2024)
The psychological features of perception of primary school children as a psychological category are considered. Specific manifestations and essential age patterns of perception in the system of cognitive development of primary schoolchildren are determined. The role of perception as a factor in the harmonious formation of the child’s personality during the period of study in primary school is determined. The psychologically significant reasons for the vulnerability of child development, including cognitive development, in wartime are analysed. Special attention is paid to understanding the specific requirements for the implementation of a system of psychological support for the development of primary school children in the conditions of staying in the frontline areas and forced migration. In particular, it is about taking into account the needs of adaptation and living conditions of children who were forced to migrate as a result of military aggression against Ukraine. An empirical study of the peculiarities of the perception of primary school children living in Ukraine, as well as those whose families have received temporary asylum from the war in Denmark, was conducted. The study was carried out using the psychodiagnostic methods «What is missing in these pictures» and «What objects are hidden in the picture», which are intended for primary school children. Fisher’s angular criterion was used to calculate the data obtained. It has been empirically proven that psychological support for the cognitive development of primary school children should be based on the factor of place of residence. In particular, children who have been forced to migrate as a result of military aggression against Ukraine partially show a lower level and need support in the development of perception.